Pancreatitis Is a Silent Killer in Peritoneal Dialysis With Difficult Diagnostic Approach. Issue 11 (26th March 2018) - Aliotta, Roberta; Zanoli, Luca; Lauretta, Itria; Giunta, Rosa; Ferrario, Silvia; Rastelli, Stefania; Rapisarda, Sebastiano; Rahbari, Elnaz; Rapisarda, Francesco
Until 2018, 236 cases of acute pancreatitis have been reported in patients who underwent peritoneal dialysis. Here, we presented a patient with double renal transplantation with chronic renal failure, under renal replacement therapy by peritoneal dialysis, who developed acute pancreatitis with abdominal pain, nausea, vomiting, leukocytosis with neutrophil left shift which is complicated by pancreatic pseudocyst, candida peritonitis, fungal sepsis, overlapping of Acinetobacter baumannii sepsis, and pneumonitis. After the percutaneous cystogastrostomy drainage of pancreatic pseudocyst, changes from peritoneal dialysis to hemodialysis, various thoracentesis, and polyantibiotics therapy, the resolution of the sepsis state was seen. The particular aspect of our case is the various comorbidity risks, severe pancreatitis associated with candida and A baumannii sepsis, and treatment strategy that lead to heal this kind of the high mortality rate condition.